Higgs modulation of emergent mass as revealed in kaon and pion parton distributions - Cui, Zhu-Fang; Ding, M.; Gao, Fei; Raya, K.; Binosi, D.; Chang, L.; Roberts, C. D.; Rodríguez-Quintero, J.; Schmidt, S. M. (The European physical journal. A, Hadrons and nuclei, 2021)
Strangeness was discovered roughly seventy years ago, lodged in a particle now known as the kaon, K. Kindred to the pion, π; both states are massless in the absence of Higgs-boson couplings. Kaons and pions are Nature’s most fundamental Nambu-Goldstone modes. Their properties are largely determined by the mechanisms responsible for emergent mass in the standard model, but modulations applied by the Higgs are crucial to Universe evolution. Despite their importance, little is known empirically about K and πstructure. This study delivers the first parameter-free predictions for all K distribution functions (DFs) and comparisons with the analogous πdistributions, i.e. the one-dimensional maps that reveal how the light-front momentum of these states is shared amongst the gluons and quarks from which they are formed. The results should stimulate improved analyses of existing data and motivate new experiments sensitive to all K and πDFs.
Gesehen am 23.02.2021